Structural characterization and inhibition on α-glucosidase of the polysaccharides from fruiting bodies and mycelia of Pleurotus eryngii - Zheng, Xiaomin; Sun, Huiqing; Wu, Lingran; Kong, Xiangru; Song, Qiaoying; Zhu, Zhenyuan (International journal of biological macromolecules, 2020)
The Pleurotus eryngii was chose as research subject to study the similarity and discrepancy of polysaccharides from fruiting body and mycelia, which were named as PEBP-II and PEMP-II, respectively. The purpose is to expand the production and application of Pleurotus eryngii polysaccharide. The molecular weights of PEBP-II and PEMP-II were 4.062 × 106 Da and 4.189 × 106 Da, respectively. The PEBP-II was composed of α-d-Glcp(1→, →6)-β-d-Galp(1→, →4)-α-d-Glcp(1→, →3,4)-α-d-Glcp(1→ and →3)-α-d-Manp(1→. The PEMP-II was composed of α-d-Glcp(1→, →6)-β-d-Galp(1→,→4)-α-d-Glcp(1→, →3,4)-α-d-Glcp(1→, →3)-α-d-Manp(1→, →3, 6)-α-d-Manp(1→ and →3)-α-d-Glcp(1→. The PEBP-II and PEMP-II both had dendritic and filamentous structure. The difference of PEBP-II and PEMP-II in structure was the ratio and kinds of backbone and branches. The PEBP-II and PEMP-II had equivalent inhibition on α-glucosidase and can significant inhibit the activity of α-glucosidase with inhibition types of competitive. All the results revealed that the polysaccharides from mycelia can be an effective substitute of polysaccharides from fruiting body. The manuscript expanded the production and application of Pleurotus eryngii polysaccharide. The analysis of chemical structure can provide theoretical basis for exploring the structure-activity relationship of polysaccharides. •The polysaccharides from fruiting body and mycelia have high similarity.•Two polysaccharides have difference in the ratio of backbone and branches.•Two polysaccharides can significant inhibit the activity of α-glucosidase.•Two polysaccharides have equivalent inhibition on α-glucosidase.•Polysaccharide from mycelia can substitute the polysaccharide from fruiting body.